The utility of FDG-PET in the differential diagnosis of Parkinsonism. (3rd August 2017) - Brajkovic, Leposava; Kostic, Vladimir; Sobic-Saranovic, Dragana; Stefanova, Elka; Jecmenica-Lukic, Milica; Jesic, Ana; Stojiljkovic, Milica; Odalovic, Strahinja; Gallivanone, Francesca; Castiglioni, Isabella; Radovic, Branislava; Trajkovic, Goran; et al.
Abstract: Introduction: Differential diagnosis of parkinsonian disorders can be difficult on clinical grounds, especially in the early stage. Recent advancements in 18-F-fluorodeoxyglucose positron emission tomography (FDG-PET) imaging reveals different patterns of regional glucose metabolism in idiopathic Parkinson's disease (IPD) and atypical parkinsonian syndromes, such as multiple system atrophy (MSA), progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS), which may help differentiating between these conditions. Purpose: To assess the utility of FDG-PET imaging in differential diagnosis of Parkinsonism in clinical practice. Methods: FDG-PET was performed in 72 patients with parkinsonism (age 34–80 years) referred to our center by movement disorder specialists. FDG-PET diagnosis was obtained by visual assessment of individual scans combined with voxel-based statistical parametric mapping analysis. FDG-PET diagnosis assigned at the time of imaging was compared with the final clinical diagnosis made by the movement disorder specialists after ≥2 years follow-up. Results: FDG-PET findings were consistent with IPD in 27, MSA in 18, PSP in 19 and CBS in 2 patients. The final clinical diagnosis was IPD in 29, MSA in 20, PSP in 21 and CBS in 2 patients. Concordance between the FDG-PET and clinical diagnoses was 92% in the overall sample (IPD 93%, MSA 90%, PSP 91% and CBS 100%). The diagnostic accuracy of FDG-PET was 93% for IPD and MSA and 97% for PSP. Conclusion: FDG-PET may help differentiate between IPD, MSA, PSP and CBS among patients presenting with parkinsonian symptoms, which is important for patient counselling and making early decisions about treatment.